Innovative Learning Experience: A Platform for Engaged Education - C., Sudheer Kumar; Bukkacherla, Manasa; Challa, Mounika Anumpalli; Rayachur, Chandrasekhar; Malupeddi, Mahesh (Recent Research Reviews Journal, 2025)
This paper presents Knowledge Hub, an advanced Learning Management System (LMS) designed to address critical challenges in digital learning, including limited personalization, low user engagement, and scalability issues. Distinct from conventional platforms, this LMS integrates real-time analytics, role-based access, personalized learning paths, and video-based content delivery to optimize user experience and learning outcomes. In an initial implementation involving 150 learners, the platform achieved a 72% course completion rate, an improvement from a baseline of 47%, and received an average user satisfaction rating of 4.4 out of 5. Additionally, it supports adaptive content delivery, live feedback, and collaborative learning, contributing to a more inclusive and effective educational environment. These results underscore the system’s potential to address existing gaps in online learning and provide a scalable, user-friendly alternative to traditional LMS solutions.